2020
DOI: 10.1016/j.lmot.2020.101656
|View full text |Cite
|
Sign up to set email alerts
|

Pulling for pleasure? Erotic approach-bias associated with porn use, not problems

Abstract: Background and Objectives: Addictive behaviors are gaining recognition in the clinical community, leading to more attention for the effects of problematic porn use. As many addictive behaviors are characterized by automatically activated approach-tendencies for disorder-relevant stimuli, we tested whether such tendencies are also present for erotic images and whether these are related to problematic porn use. Methods: Measuring approach-bias for erotic photographs, sixty-two healthy heterosexual and bisexual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Furthermore, in males but not in females, individuals with PPU demonstrated stronger approach bias toward sexual stimuli than non-problematic pornography users: in particular, problematic pornography users showed more than a 200% stronger approach bias than individuals without PPU. Finally, Kahveci et al (2020) found that individuals reporting using pornography on a more regular basis showed stronger approach biases towards sexual stimuli; however, severity of pornography consumption (measured through the Problematic Pornography Use Scale –PPUS–) did not significantly correlate with approach bias, and problematic and non-problematic pornography users did not differ in terms of approach biases toward sexual stimuli. These findings suggest that frequency –but not severity– of pornography consumption may constitute the key factor when predicting approach biases toward sexual stimuli.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, in males but not in females, individuals with PPU demonstrated stronger approach bias toward sexual stimuli than non-problematic pornography users: in particular, problematic pornography users showed more than a 200% stronger approach bias than individuals without PPU. Finally, Kahveci et al (2020) found that individuals reporting using pornography on a more regular basis showed stronger approach biases towards sexual stimuli; however, severity of pornography consumption (measured through the Problematic Pornography Use Scale –PPUS–) did not significantly correlate with approach bias, and problematic and non-problematic pornography users did not differ in terms of approach biases toward sexual stimuli. These findings suggest that frequency –but not severity– of pornography consumption may constitute the key factor when predicting approach biases toward sexual stimuli.…”
Section: Resultsmentioning
confidence: 89%
“…The first step of decision making is also influenced by another cognitive process: approach bias toward appetitive stimuli. Approach bias is defined as “ an automatically activated action tendency to approach reward-related cues ” ( Kahveci, van Bocstaele, Blechert, & Wiers, 2020, p. 2 ). The most popular paradigm to assess this aspect is the approach-avoidance task (AAT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we used the Mann-Whitney U test to examine differences in gender and marital status, and Spearman correlations to evaluate the relationship between the PPUS-J and sexual, gaming, and Internet behaviors, and the SCS, GAS, CIUS, K6, TIL, and SDISS to examine convergent and divergent validity. Furthermore, although the PPUS does not have a specified validated cutoff score, in previous studies participants with a PPUS score of 28 or higher were classified as problematic pornography users (Kahveci et al, 2020;Sklenarik et al, 2019). Therefore, in this study, individuals with a PPUS-J score of 28 or higher were classified as problematic pornography users.…”
Section: Data Analysesmentioning
confidence: 79%